Question of the Interpretation of Presidential Inauguration Institute by the Constitution of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article deals with the question of responsibility for violating the National Fund of Kazakhstan. The authors raise the question about the risks associated with the height of opportunities for corruption and misuse of funds of the Fund. The paper proposes to develop a system of criminal law units to counter misuse of funds of the National Fund.Key words: National Fund, the stabilization fund, anti-corruption, official, abuse of public power, the object of criminal legal protection, transfer.